Terrorism and the Liberal State - Wilkinson, Paul. (London, 1977)
There have been encouraging signs over the past few years of a growth of scholarly interest in the phenomenon of political terrorism. Surely it is not entirely coincidence that this has oc curred when the incidence of terrorism in many parts of the world has been dramatically increasing. It has never been my view that it is improper or demeaning for academics to interest themselves in the urgent practical problems of the day. Indeed in discussing the problem of terrorism with members of the public, politicians, officials, members of security forces and fellow academics, one is im pressed by the widespread desire for serious analysis and long-term thinking concerning the nature of terrorist phenomena, their causes, effects and policy implications for Western governments and societies. The present book is an attempt to contribute to this analysis and to stimulate further debate through an investigation of the problem of terrorism from a liberal democratic perspective, and to suggest some practicable and effective means of tackling it.
Keywords: Terrorism